2003
DOI: 10.1007/s00467-003-1219-9
|View full text |Cite
|
Sign up to set email alerts
|

Vesicoureteric reflux in Kuwaiti children with first febrile urinary tract infection

Abstract: The prevalence of vesicoureteric reflux (VUR) in children with urinary tract infection (UTI) varies among different racial groups. The purpose of this study was to determine the frequency of VUR and associated renal changes in a group of Arab Kuwaiti children with their first documented febrile UTI and to compare our findings with those reported from other racial groups. One hundred and seventy-four children (38 males and 136 females) fulfilled the study criteria and were divided into three age groups (<1 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
(24 reference statements)
2
4
0
4
Order By: Relevance
“…In a study from USA Chand et al found that age wise incidence of VUR was 52% in 0-2 years, 26% in 3-6 years, 18% in 7-11 years and 4% in 12-21 years of age. 2 Similar result was found by Zaki et al 31 In our study, the incidence and severity of grades of VUR in children is higher than the studies done by Chand et al and Zaki et al 2,31 The lack of antenatal sonologic evaluation and late referral of the patients are the two important risk factors that differs the present study with others. 32,33 In our study grade III-V reflux was present in 31 renal units which comprises 88.56% of the refluxing units .This figure is much higher than the study by Orellana P et al where moderate to severe grades were present in43.16% kidneys.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a study from USA Chand et al found that age wise incidence of VUR was 52% in 0-2 years, 26% in 3-6 years, 18% in 7-11 years and 4% in 12-21 years of age. 2 Similar result was found by Zaki et al 31 In our study, the incidence and severity of grades of VUR in children is higher than the studies done by Chand et al and Zaki et al 2,31 The lack of antenatal sonologic evaluation and late referral of the patients are the two important risk factors that differs the present study with others. 32,33 In our study grade III-V reflux was present in 31 renal units which comprises 88.56% of the refluxing units .This figure is much higher than the study by Orellana P et al where moderate to severe grades were present in43.16% kidneys.…”
Section: Discussionsupporting
confidence: 89%
“…17,18,20,24 Zaki et al found the incidence of reflux 22%. 31 This difference may be due to that our country and India have more or less similar geographical, cultural and socioeconomic background and both the studies were done in tertiary level hospital and the patients reach there late due to parental ignorance, poverty and late referral by the primary and secondary care givers. In this study higher frequency of VUR has been found in older children (Table IV).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown that radiological abnormalities exist in as many as 25-55% of children after their first UTI, with one-third having VUR [4][5][6][7][8][9][10]. There was a high incidence of acute pyelonephritis (APN) in the presence of VUR, but APN does not necessarily need VUR for its development.…”
Section: Introductionmentioning
confidence: 96%
“…Among them, 16% of patients were diagnosed with VUR grade I and II, while 19.5% of the cases were diagnosed with VUR III-V. This is slightly higher than that reported in Turkey (19.4) and lower than that found in Kuwait (33%) (6,18,22,23). All patients with grade I and II were referred to the pediatric department for follow-up and they were excluded from this study, whereas higher grades were corrected endoscopically.…”
Section: Discussionmentioning
confidence: 76%